A pilot randomized controlled trial of telephone-based cognitive behavioural therapy for preoperative bariatric surgery patients. (May 2016) - Cassin, Stephanie E.; Sockalingam, Sanjeev; Du, Chau; Wnuk, Susan; Hawa, Raed; Parikh, Sagar V.
Abstract: Background: Psychosocial interventions can improve eating behaviours and psychosocial functioning in bariatric surgery candidates. However, those that involve face-to-face sessions are problematic for individuals with severe obesity due to mobility issues and practical barriers. Objective: To examine the efficacy of a pre-operative telephone-based cognitive behavioural therapy (Tele-CBT) intervention versus standard pre-operative care for improving eating psychopathology and psychosocial functioning. Methods: Preoperative bariatric surgery patients ( N = 47) were randomly assigned to receive standard preoperative care ( n = 24) or 6 sessions of Tele-CBT ( n = 23). Results: Retention was 74.5% at post-intervention. Intent-to-treat analyses indicated that the Tele-CBT group reported significant improvements on the Binge Eating Scale (BES), t (22) = 2.81, p = .01, Emotional Eating Scale (EES), t (22) = 3.44, p = .002, and Patient Health Questionnaire-9 (PHQ-9), t (22) = 2.71, p = .01, whereas the standard care control group actually reported significant increases on the EES, t (23) = 4.86, p < .001, PHQ-9, t (23) = 2.75, p = .01, and General Anxiety Disorder-7 (GAD-7), t (23) = 2.93, p = .008 over the same time period. Conclusions: Tele-CBT holds promise as a brief intervention for improving eating psychopathology and depression in bariatric surgery candidates. Highlights: We compare telephone-based CBT (Tele-CBT) to standard pre-operative care. We examine changes in eating psychopathology following Tele-CBT. We examine changes in psychosocial functioning following Tele-CBT. Tele-CBT improves eating psychopathology and depression more than standard care. Tele-CBT improves treatment accessibility for obese bariatric surgery patients.